Study of Electrochemical Transformation of Anacardic Acid from Cashew (Anacardium occidentale) Nut Shell Liquid - Alvaro A. Arrieta; Jorge A. Ducuara; Yamid Nuñez de la Rosa (Molecules)
The valorization of agricultural waste has gained attention due to the need for sustainable technologies addressing environmental and economic challenges. The aim of this work is to investigate the electrochemical transformation of anacardic acid, a major component of cashew nut shell liquid (CNSL), into organic acids and polymeric materials. Cyclic voltammetry (CV) was carried out on ethanolic anacardic acid solutions with NaOH as the supporting electrolyte to induce oxidation reactions. CV, FTIR spectroscopy, and electrochemical impedance spectroscopy (EIS) were used to analyze the transformation processes. The results revealed oxidation sequences involving phenoxyl radicals, hydroquinones, and benzoquinones, leading to ring-opening reactions and the production of low-molecular-weight organic acids, including propionic, formic, oxalic, lactic, and acetic acids, as confirmed by HPLC. Polymerization processes were also observed, leading to the attainment of polymeric materials. FTIR spectra showed changes in phenol and carboxylic acid bands, confirming chemical transformations. CV and EIS indicated irreversible oxidation processes with charge transfer coefficients between 0.397 and 0.414 controlled by diffusion–adsorption. This work demonstrates the feasibility of electrochemical oxidation as a green method for producing organic acids from anacardic acid, aligning with circular economy principles and reducing reliance on petrochemical sources. It highlights the potential of electrochemical approaches for sustainable biomass utilization and fine chemical synthesis.